PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI SAMSAT KABUPATEN BENGKULU SELATAN - Wahyudin, Sapto; Darma, Dito Aditia (Merwin Publisher, 2025)
Employee performance is one of the key factors that determine operational effectiveness and efficiency within an organization. In this context, the roles of motivation and work discipline become important and interesting to study further. This study aims to analyze the influence of motivation and work discipline on the performance of employees at SAMSAT Kabupaten Bengkulu Selatan. The research method is qualitative, with subjects consisting of administrative staff, supervisors, and senior management at SAMSAT Kabupaten Bengkulu Selatan. Data collection was conducted through in-depth interviews, observations, and documents, with data analysis conducted using qualitative data analysis techniques. The findings show that motivation and work discipline indeed play important roles in the performance of SAMSAT Kabupaten Bengkulu Selatan employees. Motivation, whether arising from financial incentives or recognition and appreciation for hard work, shows a significant influence in encouraging employees to work better. Meanwhile, work discipline is also proven to play a crucial role in employee performance, with employees who comply with regulations and work procedures tending to be more productive and efficient in carrying out their tasks. This study recommends that SAMSAT Kabupaten Bengkulu Selatan continue to promote and maintain the level of employee motivation through fair and equitable incentives, as well as recognition and appreciation for their hard work. On the other hand, the organization also needs to ensure the consistent and fair application and enforcement of work discipline to create a conducive and productive work environment.